2021
DOI: 10.7759/cureus.16047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Homeostatic Model Assessment-Insulin Resistance, Anti-Mullerian Hormone, and BMI in the Characterization of Polycystic Ovary Syndrome

Abstract: Bahadur et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, AMH was evaluated in women with polycystic ovarian syndrome, and was found to be significantly and negatively correlated with BMI and waist-to-height ratio [ 28 ]. The mechanisms underlying this inverse correlation between AMH and BMI are still unclear, though the impact of insulin resistance on follicular development in PCOS has been speculated [ 29 ]. Interestingly, it has been suggested that the inverse relationship between serum levels of AMH and BMI could be the result of hormone dilution due to higher blood volume in women with elevated BMI [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AMH was evaluated in women with polycystic ovarian syndrome, and was found to be significantly and negatively correlated with BMI and waist-to-height ratio [ 28 ]. The mechanisms underlying this inverse correlation between AMH and BMI are still unclear, though the impact of insulin resistance on follicular development in PCOS has been speculated [ 29 ]. Interestingly, it has been suggested that the inverse relationship between serum levels of AMH and BMI could be the result of hormone dilution due to higher blood volume in women with elevated BMI [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early onset adiposity has been implicated in the pathogenesis of PCOS and can be predictive of a more severe phenotype. It is also linked to the development of low-grade inflammation, greater cardiometabolic dysfunction and future risk of atherosclerosis [12][13][14][15]. Our data shows that as an indicator of visceral fat function, VAI correlates well with severity of menstrual dysfunction and ovarian dysmorphology, and seems to be predictive of impaired glucose tolerance, thus indicating propensity for development of diabetes in the future.…”
Section: Discussionmentioning
confidence: 63%
“…Excessive insulin levels have been shown to alter granulosa cell uptake, and subsequently, AMH production. 23 In addition, the increased leptin production associated with obesity may directly suppress AMH production. This condition stems from the inhibitory effect of leptin on the expression of the AMH receptor gene.…”
Section: Discussionmentioning
confidence: 99%